Desain Homestay pada Rumah Pesisir di Pulau Lancang Besar Kepulauan Seribu - Mustikowati, Endah; Bachri, Annizar; Nimpuno, Wibisono Bagus; Permata, Suciati (CV. IRA PUBLISHING, 2024)
Residential settlements in the Lancang Besar Island area of Kepulauan Seribu, apart from being used as residences, also function as micro-trading places. Seeing the high tourism potential in this area, this residence can be developed into a homestay for visiting tourists. The implementation methods and strategies applied in this activity include field observations followed by qualitative data analysis and residential design planning by adding homestay facilities. Several important things that need to be emphasized in the design of homestays originating from residents' homes in coastal areas include spatial organization, destruction, materials, vegetation, sanitation and elements of locality. The locality aspect of this design emphasizes several concepts, including local architecture, local materials, recycled materials, and local culture. Design planning needs to consider local architecture, as well as the spatial relationship formed between the rented space and the homeowner so that the existence of the homestay is able to provide a spatial and cultural experience for tourism visitors and also improve the quality of life of the homestay owner.